Lucky lottery by Ron Roy; illustrated by John Steven Gurney By: Roy, Ron - Roy, Ron; Gurney, John, ill (New York Random House, 2000)
Dink and his two friends help Lucky find the culprit who stole Lucky's winning lottery ticket.
A Stepping Stone book.
Keywords: Lotteries-Fiction; Mystery and detective stories